2022
DOI: 10.37896/ymer21.02/52
|View full text |Cite
|
Sign up to set email alerts
|

A Non Invasive Approach to Prevent Carpel Tunnel Syndrome of IT Women during Pregnancy

Abstract: Carpal Tunnel Syndrome results in considerable discomfort and pain, limitation of activities of daily living, loss of sleep and work disability. Carpal tunnel Syndrome is more frequent in pregnancy because the systemic process increases the extra capsular fluid retention by the hormone Prolactin and produce soft tissue swelling in the later stages (third trimester) of their pregnancies. Many therapies have been advocated for treating the carpal tunnel syndrome including Mobilizations, nerve gliding, tendon gli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“… 18 found that the most common symptom among their sample was numbness (88.8%). In another research study, numbness then nocturnal pain were the most reported symptoms by patients 20 . This difference in the most reported symptom comes from the fact that Yazdanpanah et al 18 and Nageswari et al .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“… 18 found that the most common symptom among their sample was numbness (88.8%). In another research study, numbness then nocturnal pain were the most reported symptoms by patients 20 . This difference in the most reported symptom comes from the fact that Yazdanpanah et al 18 and Nageswari et al .…”
Section: Discussionmentioning
confidence: 88%
“…This difference in the most reported symptom comes from the fact that Yazdanpanah et al 18 and Nageswari et al . 20 were studies on clinically and electrophysiologically confirmed cases of CTS rather than on random individuals reporting symptoms on the BCTQ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation